Uma nova midia em cena: corpo, comunicação e clown - Machado, Maria Angela de Ambrosis Pinheiro (2005)
Abstract The study object of this thesis is the processes of communication and interaction between the actor's body and the experimentation environment by means of research of the clown language in theater. This language requires training of perception abilities, spontaneous action, playing and ad-libbing, always proceeding between everyday actions and artistical actions. The aim of this thesis is to understand this training as a communicative relation between body and the environment of theater research. The theme comprehends the possibilities for an understanding of the body as a medium, that is, a complex environment filled with signs and language which expresses, informs and communicates its relation with other environments, always associating nature and culture. The body is a medium which manipulates, multiplies, expands, exchanges, produces, retains and communicates information. This understanding is based on scientific research carried out by a transdisciplinary group of the sciences known as Cognitive Sciences and whose focus consists precisely in researching the way in which the body knows and interacts in its relationship with environment, by means of experimental protocols. In this respect, some arguments based on the hypothesis of neuroscientists Antonio Damásio, Andy Clark e Alain Berthoz will be presented. Among other aspects, these studies focus on which mechanisms the (human) organism develops to perceive, react and act in its relation with and within the world. The theoretical/practical entwinement between several knowledges supports the plausibility of the hypothesis that clown training qualifies the actor to interact with the environment in all the latter presents as unusual, different and polysemic, since both, environment and actor's body, are filled with unusual, different and surprising movements.